Oilseeds in Sudan: poised for growth - Mirghani, Mohamed Elwathig Saeed; Watkins, Catherine Bahar (The American Oil Chemists' Society (AOCS) PRESS, 2018)
After years of political turmoil and economic sanctions, Sudan appears to be poised for development. What are the opportunities and challenges in oilseed production and processing?